Desafíos y soluciones para la efectiva incorporación de cláusulas sociales a la contratación pública - Diana Gordo Cano (Revista Vasca de Administración Pública)
The paper analyzes the importance of socially responsible public procurement from the practical perspective of the validity of the contracts in which they are incorporated. In particular, the aim is to analyze the impact that the inclusion of social clauses or criteria shall have on these contracts and there are provided practical guidelines for their inclusion depending on the stage of the contract at which they are introduced. In particular, the limitations imposed on these clauses by the administrative tribunals for contractual remedies and the uncertainty that has arisen, as well as proposed solutions, are examined.